The impact of sleep toward executive functions among rapidly rotating shift nurses of emergency departments in Indonesia - Lilis Setyowati; Hsiao-Yean Chiu; Anggraini Dwi Kurnia; Nur Aini; Erma Wahyu Mashfufa; Ollyvia Freeska Dwi Marta (Healthcare in Low-resource Settings, 2023)
Sleep problems are significant and are closely related to attention issues, impacting executive function disorders, especially among healthcare professionals, including nurses. In contemporary times, shift work has emerged as a new challenge for healthcare professionals, affecting their health, wellbeing, and cognitive functions. This study aimed to investigate the relationship between sleep and executive function among staff working in the Emergency Department (ED). The research was a cross-sectional study conducted on emergency nurses (EN) from four hospitals in Malang, Indonesia. Sleep quantity parameters, including total sleep time (TST), sleep onset latency (SOL), wake after sleep onset (WASO), and sleep efficiency (SE), were collected based on 7-day sleep diaries. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Executive function was assessed using a Trail Making Test (TMT). Data analysis was carried out using one-sample T-tests and multiple linear regression with a stepwise model. Around 82% of ER have poor sleep quality (PSQI > 5). Other findings WASO, TST, and SE reported a shorter duration compared to the healthcare population, while the duration of SOL was twice as long. the sources of executive function TMT-A, TMT-B, and TMT B-A were longer, and TMT B/A was shorter than the normal population. TST was negatively related to simple (TMT-A), alternating (TMT-B), and performance difference (TMT B-A) p values =0.000. This study concludes that fast-rotating shift ED nurses experienced poor sleep and executive function. The most significant factors influencing executive function were TST and BMI.